POLA MOBILITAS PEDAGANG PASAR TRADISIONAL - Hari Lelono (Berkala Arkeologi, 1995)
Archaeological research on markets is actually very interesting to study in the context of cultural reconstruction of past societies. Archaeology in Indonesia cannot do this research by itself using an archaeological approach, but it needs support from other sciences such as sociology and anthropology. Until now, it has not been found market site in the excavation, therefore to trace a common thread is to anology the traditional markets that still exist in some areas.